2022
DOI: 10.1152/ajpheart.00530.2021
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension promotes microbial translocation and dysbiotic shifts in the fecal microbiome of nonhuman primates

Abstract: Accumulating evidence indicates a link between gut barrier dysfunction and hypertension. However, it is unclear whether hypertension causes gut barrier dysfunction or vice versa, and whether the gut microbiome plays a role. To understand this relationship, first, we cross-sectionally examined 153 nonhuman primates(NHPs), mean age 16±0.4yr and 129(84.3%) were females for cardio-metabolic risk factors and gut barrier function. This analysis identified blood pressure and age as specific factors that independently… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Nonetheless, previous studies have demonstrated the important mutual interactions between gut microbiota and hypertension in the development of hypertension, and one could be an initiator that changes the other. 14 , 15 Our study identified 4 bacterial genera that could be important in driving the overactivation of the immune system in the SHR, which could be targeted for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 97%
“…Nonetheless, previous studies have demonstrated the important mutual interactions between gut microbiota and hypertension in the development of hypertension, and one could be an initiator that changes the other. 14 , 15 Our study identified 4 bacterial genera that could be important in driving the overactivation of the immune system in the SHR, which could be targeted for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 97%
“…Glycemic and lipid measures were performed as previously described [18]. Blood pressure was measured noninvasively [18], and circulating monocyte chemoattractant protein (MCP)‐1, C‐reactive protein (CRP, R&D Systems), microbial translocation (MT) biomarker lipopolysaccharide‐binding protein (LBP)‐1 (Hycult Biotech Inc.), fatty acid binding protein (FABP)‐1 (LSBio), and soluble monocyte differentiation antigen CD14 (R&D Systems) were measured in plasma according to the manufacturers' instructions in duplicate by enzyme‐linked immunosorbent assay (ELISA).…”
Section: Methodsmentioning
confidence: 99%
“…Increased F/B ratio is often used as an indicator of gut microbial dysbiosis 54 . An increased F/B ratio has been reported in hypertensive animal models such as SHRs, 8 Ang‐II‐induced rats, 8 PAH rats, 52 hypoxia‐induced pulmonary hypertensive mice, 55 Dahl salt‐sensitive hypertensive heart failure rats, 56 stroke‐prone spontaneously hypertensive rats, 20 high‐fat‐diet l ‐NAME‐induced rats, 57 hypertensive monkeys, 58 and patients with hypertension, 8 while a decrease of F/B ratio was observed in high‐fructose‐induced salt‐sensitive hypertensive rats 47 . The F/B ratio in these studies has been described in details in Table 3.…”
Section: The Interaction Between Gut Microbiota and Hypertensionmentioning
confidence: 99%